Stomatal resistance investigations in maize - Anda, Angéla Rita; Lőke, Zsuzsanna Katalin (Acta Biologica Szegediensis, 2002)
Field experiment was carried out at Agrometeorological Research Station of Keszthely , in maize , during the season of 2001. Estimation of the site of average stomatal resistance for leaf was determined by mapping the distribution of the resistance values within the blade. Vertical distribution of resistance in different leaf levels was also registered. To validate the estimation, the simulation model of Goudriaan (1977) was applied. A satisfactory agreement, less than 10% alteration was found between the measured and simulated stomatal resistance values. Th eexact value of the stomatal resistance of plants might play important role in simulation modelling, as an unique input parameter regarding the plant-water relation.